Item analysis of thematic examination questions for grade 5 students theme 6 even semester 2021/2022 academic year in Sibolga City - Nasution, Tiflah Addina Khairiah; Sumarno, Sumarno; Sudrajat, Ajat (Jurnal Pembangunan Pendidikan: Fondasi dan Aplikasi, 2023)
This study aims to analyze the quality of test items given to grade 5 elementary school students in the even semester. This study used a qualitative approach carried out in several schools with different categories of questions, namely thematic questions and subject questions. The data collected included exam questions and student answers which were then analyzed using Microsoft Excel technology to determine the quality level of the questions tested. This analysis includes an evaluation of the validity, reliability, difficulty level, and differentiating power of each item. The results of this study are expected to provide guidance to educators and teachers in designing high-quality exam questions. Thus, it is expected that the questions prepared are not only in accordance with the curriculum, but also able to measure students' abilities accurately and fairly. This is important so that learners can understand and answer questions according to their capacity and skills. This research also contributes to efforts to improve the quality of education, especially in the preparation of more effective and meaningful evaluations.